Computer vision, imaging and computer graphics – theory and applications : International Joint Conference, VISIGRAPP 2014, Lisbon, Portugal, January 5-8, 2014, Revised selected papers /: International Joint Conference, VISIGRAPP 2014, Lisbon, Portugal, January 5-8, 2014, Revised selected papers. (2015) - Unknown
No abstract available